2015
DOI: 10.1016/j.chemosphere.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Mercury methylation in sediments of a Brazilian mangrove under different vegetation covers and salinities

Abstract: The presence and formation of methylmercury (MMHg), a highly toxic form of Hg, in mangrove ecosystems is poorly studied. Therefore the aim of this study was to evaluate mercury methylation potentials in sediment, litter and root samples (Avicennia shaueriana and Spartina alterniflora) from different regions of a mangrove ecosystem, as well as the influence of salinity on methylation. Sediment was sampled under different depths and in mangrove regions with different plant covers and salinities. All samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…No correlations were observed for salinity and MeHg concentrations in natural mangrove ecosystems (de Oliveira et al 2015) or hypersaline lakes (Johnson et al 2015). The effect of pH conditions on methylation is equally unclear.…”
Section: Salinity Ph and Trophic Statusmentioning
confidence: 91%
See 1 more Smart Citation
“…No correlations were observed for salinity and MeHg concentrations in natural mangrove ecosystems (de Oliveira et al 2015) or hypersaline lakes (Johnson et al 2015). The effect of pH conditions on methylation is equally unclear.…”
Section: Salinity Ph and Trophic Statusmentioning
confidence: 91%
“…Louis et al 1994Branfireun et al 1998Branfireun et al , 1999Tjerngren et al 2012b) and has been recently observed in wetlands in the northern Great Plains (Hoggarth et al 2015), southern Louisiana (Hall et al 2008), the high Arctic , in agricultural and non-agricultural wetlands (MarvinDiPasquale et al 2014), and temperate forests (Selvendrian et al 2008). Methylation also occurs in a number of saline, estuarine, and marine environments (e.g., Olson and Cooper 1974;Bartha 1985, 1987;Mason et al 1993), and recently it has been observed in the surface sediments of mudflats (a type of coastal wetland) (Ouddane et al 2008), mangroves (de Oliveira et al 2015), and lagoons (Bloom et al 2004;Coelho-Souza et al 2006;Monperrus et al 2007a;Faganeli et al 2012;Guédron et al 2012;Hines et al 2012). The porewaters of peatland have also been found to be a primary source of MeHg to the surrounding environment (Mitchell et al 2008a), demonstrating the importance of these minuscule interstitial spaces in larger environmental impacts.…”
Section: Wetlands and Sedimentsmentioning
confidence: 99%
“…Salinity can also be an important factor conditioning Hg Fig. 1 Map of the sub-basins of the Baltic Sea with the location of sampling stations in and the industrial hot spots in the Baltic Sea catchment area (HELCOM 2010) transformations on the water-sediment interface it can affect the methylation potential of Hg (Braaten et al 2014;Chen et al 2015;de Oliveira et al 2015;Jonsson et al 2014). Salinity can also impair the Hg adsorption onto clay minerals (Green-Ruiz 2009), thus affecting the release of Hg into the near-bottom water.…”
Section: Introductionmentioning
confidence: 99%
“…The form of Hg in marine sediments is influenced by several physicochemical processes, such as adsorption onto clay minerals and organic matter, the formation of complexes with organic and inorganic ligands, precipitation and co-precipitation (mainly mercury sulphide (HgS)), oxidation and reduction reactions and the formation of the most dangerous metal-organic compounds (mainly MeHg) (Jackson 1998 ; Bełdowski and Pempkowiak 2007 ; Bełdowski et al 2014 ). Salinity can also be an important factor conditioning Hg transformations on the water-sediment interface it can affect the methylation potential of Hg (Braaten et al 2014 ; Chen et al 2015 ; de Oliveira et al 2015 ; Jonsson et al 2014 ). Salinity can also impair the Hg adsorption onto clay minerals (Green-Ruiz 2009 ), thus affecting the release of Hg into the near-bottom water.…”
Section: Introductionmentioning
confidence: 99%
“…Waterlogged mangrove soils provide conditions for both organic matter preservation and production of Hg, through low rates of decomposition, bacterial activity and complex root–sediment geochemical interactions transforming and exporting methylmercury (MeHg) (de Oliveira et al, 2015; Silva et al, 2003). The Small Pool surface sample collected at the MG site–mangrove margin (Figures 2 and ) is where mangrove roots, saturated soil conditions, leaf litter and a mat of purple sulphur bacteria combine.…”
Section: Discussionmentioning
confidence: 99%